PERTUMBUHAN RELATIF IKAN SELAIS (Ompok sp) YANG TERTANGKAP DI SUNGAI KAMPAR DAN SUNGAI SIAK, RIAU - Putra, Ridwan Manda; ', Windarti; ', Yanti (Fakultas Perikanan dan Kelautan Universitas Riau, 2012)
A study on relative growth of Ompok sp obtained from the Kampar andSiak Rivers has been conducted on April to June 2011. This study aims tounderstand the similarity and differences of the fish that inhabit those rivers,Kampar River with good water quality and Siak River that with poor waterquality. There were 84 fishes from the Kampar River (in the Teratak Buluhvillage) and 31 fishes from the Siak River (in the Tapung village) were capturedin this study. The meristical characteristics were studied and the morphologicalcharacteristics were analyzed to understand the relative growth of the fish. Resultsshown that there were no difference in the meristical and morphologicalcharacteristics of the fishes obtained from both sampling areas and its indicate thatthe fishes sampled were belonged to a single species. Data also shown that almostall of fish’s body morphometrical characteristics grow isometrically to total lengthand it means that the fish was not showing any morphological changes as theygrow. However, in the wegth-length relationship, the b values of the fishes fromboth sampling area was less than 3 and its indicate that increasing in fish bodyweight was slower than the increment of fish total length. Based on data obtained,it can be concluded that there was no difference in relative growth pattern of fishliving in the Kampar and Siak Rivers.